Demystifying the Connection between Corporate Board Structure and Financial Performance in Maritime Firms - Kour, Manjit; Taneja, Sanjay; Ozen, Ercan (Transactions on Maritime Science, 2025)
The aim of this research is to investigate the association between the composition of corporate boards and the financial performance of companies that operate in the maritime sector. This research analyses how gender diversity, CEO duality, board size, and board independence affect the profitability and value of Indian maritime companies that have been selected as the sample for this study. This study is based on 40 maritime firms in India. Data is collected from secondary sources. Pooled regression analysis is utilised to estimate the coefficients of the variables of interest.The results reveal a positive association between board independence, gender diversity, and firm profitability, while board size is negatively linked with firm profitability as measured by ROA (return on assets). The results also point that there is a positive association between board independence, gender diversity, and firm value, while board size is negatively linked with firm value as measured by Q-Tobin. Gender diversity, board size, and board independence have significantly contributed to the performance of the company. While the benefits of gender diversity and board independence reveal how fundamental the diversified and independent boardrooms are to financial success, the evidence indicating the negative signs of association between CEO duality and firm performance suggests that a division of duties between the office of CEO and board chairperson may lead to better monitoring and decision-making.